Book review: MARINA VIGÁRIO, SÓNIA FRITA & M. JOÃO FREITAS (eds.), Phonetics and phonology: Interactions and interrelations (Current Issues in Linguistic Theory 306) – CORRIGENDUM. (11th July 2016) - Deterding, David
Abstract : The author of this book review apologies for the error in one of the book editors' names. Sónia Frita should beSónia Frota .